KOMPETENSI ABSOLUT PERADILAN TATA USAHA NEGARA DALAM SENGKETA TANAH TERHADAP SERTIFIKAT HAK ATAS TANAH - Onma Ezra Rodi Aprilo; Langgam Ihutan; Eric Halomoan; Anandersah Sinaga; Santi Hapsari Dewi Adikancana (Jurnal Hukum Peratun, 2022)
The purpose of this article is to knowing how the absolute competence of the State Administrative Court in Indonesia is and how the competence of the State Administrative Court is if there is a land dispute over land rights certificates. This article was compiled using 2 (two) types of approaches, namely the normative approach and the historical approach where this article is a normative research article. Based on the results of the discussion analysis, the absolute competence of the State Administrative Court is the authority to examine, decide, and resolve state administrative disputes where there are existing restrictions.